THE EFFECTIVENESS OF ADMINISTRATIVE LAW ENFORCEMENT IN CASES OF PALM OIL PLANTATION THEFT: A PERSPECTIVE FROM AGRARIAN REGULATIONS - Loso Judijanto (CV. Adiba Aisha Amira, 2025)
This study highlights the importance of administrative law in maintaining order and justice in the agricultural sector, with a particular focus on agrarian regulation and supervision mechanisms. Findings indicate that although administrative law provides a clear framework, challenges such as lack of coordination between agencies and minimal public understanding of agrarian regulations remain major obstacles. This study recommends enhancing education, socialisation, and inter-agency cooperation to improve the effectiveness of law enforcement. With consistent implementation and good coordination, it is hoped that the protection of oil palm plantation owners' rights can be enhanced and cases of theft minimised.